Peningkatan Pemahaman Gizi Melalui Program Gizi Kita dan Media Promosi Kesehatan untuk Pencegahan Stunting - Yasinta Indah Widyaningsih; Azharatul Jannah; Yulita Sirinti Pongtambing; Rezki Ramdani; Mahendri Deayu Putri (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
Stunting remains a chronic nutritional problem affecting children’s physical growth and cognitive development. Limited nutritional knowledge and suboptimal caregiving practices are major challenges in communities with restricted access to health information. This community service activity aimed to improve the understanding of pregnant women and mothers with toddlers through a nutrition workshop and the use of health promotion media, such as leaflets and educational calendars, as a stunting prevention strategy. The participatory education method, including interactive lectures and group discussions, was implemented in Kelurahan Jagong, Kecamatan Pangkajene, Kabupaten Pangkajene dan Kepulauan. During the discussion sessions, evaluation was conducted using a true/false method for key questions on balanced nutrition and stunting prevention. Results showed that about 75% of participants correctly answered questions on optimal maternal nutrition, while 82% correctly answered questions on appropriate toddler feeding practices. These percentages indicate that the workshop material effectively addressed practical aspects that were easily understood and directly impacted participants’ knowledge. Educational media reinforced understanding and facilitated the application of nutritional practices at home. This intervention has important implications for strengthening community and local health worker capacity and highlights the need for cross-sector collaboration to support consistent nutrition behavior change.